Interventional therapy for rectal neuroendocrine tumor with liver metastases: report of one case - Liu, Lingxiao; Han, Xu; Lou, Wenhui (Translational Gastroenterology and Hepatology, 2016)
A 42-year-old male patient was admitted due to altered bowel habit for 1 month and liver metastases found during health check-up 1 week ago. Thin stools form with reduced defecation frequency, and weight loss have been observed. Digital rectal exam found a 2–3 cm soft, clear boundary mass 5 cm above the anal verge, and colonoscopic biopsy identified this rectal tumor as nonfunctional neuroendocrine tumor (G1). Computed tomography imaging showed multiple liver metastases with rich blood supply, and the tumor burden exceeded 70%. As indicated by multidisciplinary treatment (MDT) consultations, the patient had lost the chance for radical surgery. Interventional therapy has been chosen for liver metastases and primary tumor, during which liver biopsy was performed suggesting liver metastases as neuroendocrine tumor (G2). Interventional therapy included percutaneous transcatheter arterial chemoembolization (TACE) and transcatheter arterial infusion (TAI) chemotherapy; the following chemotherapeutic agents were selectively used: oxaliplatin, irinotecan, epirubicin and Lipiodol®. After the 9th intervention, imaging evaluation indicated that liver metastases were obviously shrank, although the rectal lesion was still same as before. Currently the patient survived for nearly 2 years from baseline and was still under frequent observation. We concluded that interventional therapy targeting liver metastases and primary lesion in patients with advanced rectal neuroendocrine tumors NETs could control tumor progression and prolong the survival.